Attitudes towards collaborative learning from high school EFL students - Nguyễn Thị Phượng (Trường Đại học Trà Vinh, 2021)
The researcher would like to gain a better insight into active learning strategies exercised, especially the way students react to collaborative learning activities in English classes. First, the study attempts to determine the attitudes of students based on the ABC model when doing collaborative learning activities in English learning. Secondly, the study throws light on how gender differences, grade and areas of study affect students’ attitudes related to their emotions, actions and opinions towards collaborative learning activities.